tim x
x(x+1)*(x+6)-x^3=5x
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Ta có: \(x\left(x+1\right)\left(x+6\right)-x^3=5x\)
<=> \(\left(x^2+x\right)\left(x+6\right)-x^3=5x\)
<=> \(x^3+7x^2+6x-x^3=5x\)
<=> \(7x^2+x=0\)
<=> \(x\left(7x+1\right)=0\)
<=> \(\left[\begin{array}{nghiempt}x=0\\7x+1=0\end{array}\right.\)<=>\(\left[\begin{array}{nghiempt}x=0\\x=-\frac{1}{7}\end{array}\right.\)
Vậy x\(\in\left\{-\frac{1}{7};0\right\}\)
\(x\left(x+1\right)\left(x+6\right)=\left(x^2+x\right)\left(x+6\right)=x^3+6x^2+x^2+6x=x^3+7x^2+6x\)
Do đó \(x\left(x+1\right)\left(x+6\right)-x^3=\left(x^3+7x^2+6x\right)-x^3=7x^2+6x\)
\(\Rightarrow7x^2+6x=5x\Rightarrow7x^2=-x\Rightarrow7=\frac{-x}{x^2}=\frac{-x}{\left(-x\right).\left(-x\right)}=\frac{1}{-x}\)
\(\Rightarrow-x=\frac{1}{7}\Rightarrow x=-\frac{1}{7}\)
x(x+1)(x-6)-x3 = 5x
<=>(x2+x)(x-6)-x3=5x
<=>x3-6x2+x2-6x-x3=5x
<=>-5x2-6x=5x
<=>-5x2-6x-5x=0
<=>-5x2-11x=0
<=>-x.(5x-11)=0
<=>x=0 hoặc 5x-11=0
<=>x=0 hoặc x=11/5
x(x+1)(x+6)-x^3=5x
(x^2+x)(x+6)-x^3=5x
x^3+6x^2+x^2+6x-x^3-5x=0
7x^2+x=0
x(7x+1)=0
x=0 hoặc 7x+1=0<=> x=-1/7